2014
DOI: 10.4049/jimmunol.1302537
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphatase Holoenzyme PP1/GADD34 Negatively Regulates TLR Response by Inhibiting TAK1 Serine 412 Phosphorylation

Abstract: The molecular mechanisms that fine tune TLRs responses need to be fully elucidated. Protein phosphatase-1 (PP1) has been shown to be important in cell death and differentiation. However, the roles of PP1 in TLR-triggered immune response remain unclear. In this study, we demonstrate that PP1 inhibits the activation of the MAPK and NF-κB pathway and the production of TNF-α, IL-6 in macrophages triggered by TLR3, TLR4, and TLR9 in a phosphatase-dependent manner. Conversely, PP1 knockdown increases TLRs-triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
2
42
1
Order By: Relevance
“…However, some studies have shown that the phosphorylation of these sites is insufficient for TAK1 activation (14,15). Consistent with this notion, our recent investigation with PP1 implied that the phosphorylation of TAK1 Ser-412 is important for TAK1 activation and function (30).…”
Section: The Phosphorylation Of Tak1 Ser-412 Is Essential For Tlrsupporting
confidence: 71%
See 2 more Smart Citations
“…However, some studies have shown that the phosphorylation of these sites is insufficient for TAK1 activation (14,15). Consistent with this notion, our recent investigation with PP1 implied that the phosphorylation of TAK1 Ser-412 is important for TAK1 activation and function (30).…”
Section: The Phosphorylation Of Tak1 Ser-412 Is Essential For Tlrsupporting
confidence: 71%
“…In summary, the present study together with our recent report (30) showing a negative regulation of TAK1 by the phosphatase PP1-GADD34 complex provided strong evidence that TAK1 activation required the phosphorylation of TAK1 Ser-412 in the IL-1R and TLR signaling pathways. PKA kinases, by directly phosphorylating TAK1, were found to be important regulators of proinflammatory and innate immune responses.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…69,70 We used Western blotting to analyze the total and Ser412-phosphorylated forms of TAK1 in stably transduced CEM.NKR-CCR5 cells (Fig. 3A).…”
Section: Tak1 Is Not Activated In Trim5a-transduced Cellsmentioning
confidence: 99%
“…A high expression of GADD34 can dramatically decrease the susceptibility of Oca2-null melanocytes to thapsigargin [27]. It can also prevent the cell damage after TLR stimulation and inflammation [28]. Thus, GADD34 upregulation may function as a protective mechanism in cells under ER stress.…”
Section: Introductionmentioning
confidence: 98%